Dissection-independent production of a Plasmodium sporozoites from whole mosquitoes - Blight,J; Sala,K; Atcheson,E; Kramer,H; El-Turabi,A; Coelho,Real E; Dahalan,F; Bettenbourt,P; Dickinson-Craig,E; Alves,E; Salman,A; Janse,C; et al. (Life Science Alliance, 2021)
Progress towards a protective vaccine against malaria remains slow. To date, only limited protection has been routinely achieved following immunisation with either whole-parasite (sporozoite) or subunit-based vaccines. One major roadblock to vaccine progress, and to pre-erythrocytic parasite biology in general, is the continued reliance on manual salivary gland dissection for sporozoite isolation from infected mosquitoes. Here, we report development of a multi-step method, based on batch processing of homogenised whole mosquitoes, slurry, and density-gradient filtration, which combined with free-flow electrophoresis rapidly produces a pure, infective sporozoite inoculum. Human-infective Plasmodium falciparum and rodent-infective Plasmodium berghei sporozoites produced in this way are two- to threefold more infective than salivary gland dissection sporozoites in in vitro hepatocyte infection assays. In an in vivo rodent malaria model, the same P. berghei sporozoites confer sterile protection from mosquito-bite challenge when immunisation is delivered intravenously or 60–70% protection when delivered intramuscularly. By improving purity, infectivity, and immunogenicity, this method represents a key advancement in capacity to produce research-grade sporozoites, which should impact delivery of a whole-parasite based malaria vaccine at scale in the future.